Descriptive epidemiology of the head and neck cancers in old patients - Gatta, Gemma; Capocaccia, Riccardo; Botta, Laura (Frontiers in Oncology, 2023)
In Europe, as in the high income (HI) countries, quite half of the newly diagnosed patients with head and neck (H&N) cancers are older than 65 years of age and their proportion within the prevalent cases is even higher. Moreover, the incidence rate (IR) for all H&N cancers sites increased with age and their survival is lower in older patients (≥65), comparing with the younger (<65). The number of older patients affected by H&N cancers will increase because of the increase of the life expectancy. The aim of the article is to provide an epidemiological description of the H&N cancers in the elderly population. Incidence and prevalence data by time period and continents was extracted from Global Cancer Observatory. Survival information for Europe is obtained, from the EUROCARE and RARECAREnet projects. In 2020, slightly more than 900,000 cases have been diagnosed with H&N cancers in the world, of them about 40% were older than 65 years of age. This percentage was higher, reaching almost 50% in the HI countries. The highest number of cases were in the Asiatic populations, while the highest crude IR were in Europe and Oceania. Among H&N cancers occurring in the elderly, laryngeal and oral cavity cancers were the most common, the nasal cavities and nasopharyngeal cancers were the rarest. This was true for all the countries, excluding some Asiatic populations, in which tumour of nasopharynx is more common. Five-year survival, in the European population was low in the elderly compared with the younger for all the H&N cancers and ranged from about 60% for both salivary gland type and laryngeal, to 22% for hypopharyngeal tumours. Conditional 5-year survival, after surviving one year, for the elderly, became more than 60% for many H&N epithelial tumours. The high variability in the H&N cancer incidence around the world is due to the distribution of the major risk factors that for the elderly are mainly alcohol and smoking. The reasons for a low survival in the elderly are most likely due to complexity of treatment, late arrival of patients at diagnosis and the difficult access to specialised centres.